Why we live where we live - Vermond, Kira (Owlkids Books, 2014)
A sweeping journey through time and space to examine places that humans choose to call home. We are influenced by many factors--the availability of food and water, the jobs we seek, the need for safety and security. But we in turn influence our environment--intentionally or not--adapting the planet to suit our needs.